Increased VLCFA-lipids and ELOVL4 underlie neurodegeneration in frontotemporal dementia - Ying He (Nature Portfolio, 2021)
Abstract Rare, yet biologically critical, lipids that contain very long chain fatty acids (VLCFA-lipids) are synthesized in the brain by the enzyme ELOVL4. High levels of VLCFA-lipids are toxic to cells and excess VLCFA-lipids are actively removed by ABCD1 in an ATP-dependent manner. Virtually nothing is known about the impact of VLCFA-lipids in neurodegenerative diseases. Here, we investigated the possible role of VLCFA-lipids in frontotemporal dementia (FTD), which is a leading cause of younger-onset dementia. Using quantitative discovery lipidomics, we identified three VLCFA-lipid species that were significantly increased in FTD brain compared to controls, with strong correlations with ELOVL4. Increases in ELOVL4 expression correlated with significant decreases in the membrane-bound synaptophysin in FTD brain. Furthermore, increases in ABCD1 expression correlated with increases in VLCFA-lipids. We uncovered a new pathomechanism that is pertinent to understanding the pathogenesis of FTD.